(untitled) (Medico Legal Update, 2020)
Intimate partner violence is any act of gender-based violence that results in, or is likely to result in, physical, sexual, or mental harm or suffering to women, including threats of such acts, coercion or arbitrary deprivation of liberty, whether occurring in public or in private life. A study was conducted to assess IPV and to find the association between IPV and selected demographic variables. Majority of the samples experienced IPV. Duration of marital life, age of the woman, spouse’s occupation, family monthly income were associated with IPV.